Carcass traits of slow-growing broiler chickens: Carijó and Label Rouge - Vaccaro, Brenda Chagas; Lima, Heder José D’Ávila; Morais, Marcos Vinícius Martins; Valentim, Jean Kaique; Bittencourt, Tatiana Marques; Moraleco, Debora Duarte; Silva , Nayara Emanoelle Matos e; Quirino, Caio Silva; Amaral, Elieverson Firmiani de Freitas; Cruz, Maira Santos da (Revista de Ciências Agroveterinárias, 2023)
The objective of this study was to evaluate the carcass characteristics of male and female broilers from the free-range strains Carijó and Label Rouge. A total of 168-day-old chicks from the two strains were used and distributed in a completely randomized design, following a 2 x 2 factorial scheme. The factors considered were sex (males and females) and strain (Carijó and Label Rouge), with seven replications and 12 birds in each experimental unit (six males and six females). Significant differences were observed between the sexes (p<0.05), with male broilers exhibiting higher live weight at slaughter, as well as greater weights of whole and marketable carcasses and cuts (thigh, drumstick, and wing), irrespective of strain. Among the female birds, those from the Label Rouge strain displayed higher yields of wings, whole carcasses, and marketable cuts compared to Carijó females (p<0.05). Additionally, thigh yield was higher in males, while breast yield was higher in females (p<0.05). Label Rouge birds also demonstrated significantly higher breast and thigh yields (p<0.05). Broilers from the Label Rouge strain showed better results for carcass and cuts yield than Carijó birds, as well as male broilers obtained better results than females.